2022
DOI: 10.1021/acs.inorgchem.2c02959
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Luminescent Organotin(IV) Complexes: Synthesis, Photophysical Characterization, and Live Cell Imaging

Abstract: Five fluorescent ONO donor-based organotin(IV) complexes, [Sn IV (L 1−5 )Ph 2 ] (1−5), were synthesized by the onepot reaction method and fully characterized spectroscopically including the single-crystal X-ray diffraction studies of 2−4. Detailed photophysical characterization of all compounds was performed. All the compounds exhibited high luminescent properties with a quantum yield of 17−53%. Additionally, the results of cellular permeability analysis suggest that they are lipophilic and easily absorbed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 106 publications
1
43
0
Order By: Relevance
“…The hydrophobicity of 1 – 4 is considered to be a key factor related to their cellular uptake and anticancer activity. ,, Because of the luminescent properties, here, the internalization of 1 – 4 was investigated by the live-cell confocal microscope assay. The blue fluorescence in the cytoplasm region (Figure S31) suggested that 1 – 4 can efficiently enter into HT-29 cells after 1 h of incubation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobicity of 1 – 4 is considered to be a key factor related to their cellular uptake and anticancer activity. ,, Because of the luminescent properties, here, the internalization of 1 – 4 was investigated by the live-cell confocal microscope assay. The blue fluorescence in the cytoplasm region (Figure S31) suggested that 1 – 4 can efficiently enter into HT-29 cells after 1 h of incubation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, compounds with higher hydrophobic behavior have a higher tendency to gather in the lipid organelles like mitochondria owing to their negative potential difference across the membrane. 47,129,130 Induction of Mitochondrial Dysfunction. Mitochondrial integrity can be investigated by the mitochondrial membrane potential (MMP, ΔΨ m ) assay using rhodamine 123 (Rh123), an MMP-specific dye, which leaks out from mitochondria after the weakening of the MMP.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[4] However, toxicity and chemoresistance as well as other side effects of cisplatin have become one of the alarming obstacles to limit its long-term application. [5] Consequently, studies on the biological activity of other non-platinum metal-based active compounds, based on tin (IV), [6] iridium (III), [7] titanium (IV), [8] and ruthenium (II/III), [9] have been attracted significant interest in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of heavy main group complexes, mainly group 14 and 15, showing beside conventional fluorescence, 12,13 phosphorescence and/or thermally activated delayed fluorescence (TADF), 10,14–16 are rare. 17–19 Emission is often limited to frozen solutions or even to the solid state, precluding bimolecular reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…For 3d TMCs, the underlying photophysical processes are well understood and groundbreaking progress was achieved in the last few years. [1][2][3][4][5] Examples of heavy main group complexes, mainly group 14 and 15, showing beside conventional uorescence, 12,13 phosphorescence and/or thermally activated delayed uorescence (TADF), 10,[14][15][16] are rare. [17][18][19] Emission is oen limited to frozen solutions or even to the solid state, precluding bimolecular reactivity.…”
Section: Introductionmentioning
confidence: 99%